Сенсор на основі напівпровідникових наноструктур для вимірювання вмісту органічних канцерогенів у об'єктах навколишнього середовища - Сушко, О. А.; Білаш, О. М.; Рожицький, М. М. (ХНУРЭ, 2012)
In abstract a problem is considered concerning the definition in environmental objects of organic carcinogens such as polycyclic aromatic hydrocarbons (PAH) and their effect for human organism. Nanophotonic sensor for organic carcinogens detection is developed. It represents portable device which is based on semiconductor quantum dots (QDs). QDs are the detector elements of nanophotonic sensor for PAH detection. The principle of nanophotonic sensor operation is based on electrochemical methods using modern nanomaterials and nanotechnologies. The working of nanophotonic sensor is based on process of QDs transfer to ionic forms in a consequence of electrochemical processes, subsequent reactions with oppositely charged ionic forms of the analyte – PAHs, resulting in the emission of an analytical optical signal. The number of quanta emitted at the given period of time is a measure of PAHs content. Nanophotonic sensor for PAH detection has such advantages as assay reproducibility, low limit of detection, cheapness of construction and versatility. It can be used in ecology for investigation and monitoring of water object for PAH content detection. На сьогоднішній день чітко проявляється тенденція до погіршення якості поверхневих і підземних вод. Проблема забруднення води органічними канцерогенами на даний момент є дуже актуальною, оскільки «канцерогенність» води, яку споживає населення України, різко зростає з року в рік. Підвищення рівня забруднення навколишнього середовища, перш за все води, продуктів харчування і т.д. хімічними органічними канцерогенами (XОК) призводить до різкого зростання кількості онкологічних захворювань не тільки в Україні, а й за її межами. За даними Всесвітньої організації охорони здоров'я щорічно кількість онкохворих збільшується на 10 млн. чоловік [1]. Україна знаходиться на другому місці в Європі за темпами поширення онкологічних захворювань. Захворюваність на рак стабільно зростає на 2,6-3% на рік, і онкозахворювання продовжують «молодіти».
Keywords: наноелектроніка; наноструктури; нанофотоніка